Faktor-Faktor yang Mempengaruhi Kepuasan Pasien BPJS Pada Pelayanan Persalinan di Puskesmas Kecamatan Pulogadung - Lina Listiani; Fevatridiyawati Fevatridiyawati (Universitas Malahayati Lampung, 2024)
ABSTRACT Satisfaction from customers is the main indicator of facility standards to be used as a measure of service quality and service quality in order to provide satisfaction to patients and customers. If the service is low, it will have an impact on customer visits and can affect the profitability of existing health facilities. However, the results of interviews with 10 patients using BPJS found that 4 (40%) said they were satisfied. Whereas in patients with a total of 6 (60%) people complained of dissatisfaction with the regulations set. To find out the Quality of Service for BPJS patients in delivery services at the Pulogadung sub-district health center in 2023. This type of research is a quantitative study of correlation research design with a cross sectional survey approach method. The research was conducted from March to May at the Batujaya Karawang Community Health Center in 2023. The population in this study were all inpatients using BPJS Health at PONED (Basic Emergency Obstetrics and Neonatal Services) in March-May 2023 with a total of 30 respondents. Sampling technique total sampling method. The data were analyzed using univariate analysis of the distribution and bivariate analysis of the chi square test. The results of univariate research from 30 respondents, overall the patient assessed as many as 19 respondents (63.3%), whereas in the majority tangible aspect, 19 respondents (63.3%) were not satisfied with the majority of 18 respondents (60.0%), in the aspect of responsiveness the majority did not satisfy as many as 20 respondents (66.7%), in the aspect of assurance the majority did not satisfy as many as 18 respondents (60.0%), in the aspect of responsiveness the majority did not satisfy as many as 20 respondents (66.7%), in the aspect of assurance the majority did not satisfy as many as 18 respondents (60.0%), in the aspect of responsiveness the majority did not satisfy as many as 20 respondents (66.7%), in the aspect of the majority, the majority aspects were not satisfying as many as 18 respondents (60.0%). In aspect empathy the majority did not satisfy 18 respondents (60.0%). The results of the bivariate study showed a relationship between age (p = 0.009), education (p = 0.015), occupation (p = 0.007), parity (p = 0.023), member status (p = 0.002), and length of time being a member (p = 0.259) with the satisfaction level of BPJS patients who receive delivery services at the Pulogadung District Health Center, Jakarta. There is a relationship between age, education, occupation, parity, BPJS status, and the satisfaction level of patients receiving delivery services. There is no relationship between being a member and the satisfaction level of patients receiving delivery services. Keywords: Patient Satisfaction, BPJS, Delivery ServicesABSTRAK Kepuasan dari pelanggan merupakan suatu adalah indikator utama pada standar fasilitas guna digunakan sebagai ukuran akan kualitas pelayanan dan mutu pelayanan guna dapat memberikan kepuasan pada pasien dan pelanggan. Apabila layanan yang rendah maka akan berdampak pada kunjungan pelanggan serta dapat berpengaruh pada protabilitas fasilitas kesehatan yang ada. Namun, Hasil wawancara dengan 10 pasien pengguna BPJS didapatkan bahwa 4 (40%) orang tersebut mengatakan dirinya merasa puas. Sedangkan pada pasien dengan jumlah 6 (60%) orang tersebut mengeluhkan kurang puas dengan adanya peraturan yang ditetapkan. Untuk mengetahui Kualitas Pelayanan pasien BPJS pada pelayanan persalinan di puskesmas kecamatan pulogadung tahun 2023. Jenis pada penelitian adalah penelitian kuantitatif desain penelitian korelasi dengan metode pendekatan cross sectional survey. Penelitian dilakukan bulan maret sampai dengan mei di Puskesmas Batujaya Karawang tahun 2023. Populasi dalam penelitian ini adalah seluruh pasien rawat inap pengguna BPJS Kesehatan di PONED (Pelayanan Obstetri dan Neonatal Emergensi Dasar) pada bulan maret-mei 2023 sebanyak 30 responden. Pengambilan sampel teknik metode total sampling. Adapun data dianalisis menggunakan Analisis univariat distribusi dan analisis bivariat uji chi square. Hasil penelitian univariat dari 30 responden, secara keseluruhan pasien menilai tidak memuaskan sebanyak 19 responden (63,3%), sedangkan pada aspek tangible mayoritas tidak memuaskan sebanyak 19 responden (63,3%), pada aspek reliability mayoritas tidak memuaskan sebanyak 18 responden (60,0%), pada aspek responsiveness mayoritas tidak memuaskan sebanyak 20 responden (66,7%), pada aspek assurance mayoritas tidak memuaskan sebanyak 17 responden (56,7%), pada aspek empathy mayoritas tidak memuaskan sebanyak 18 responden (60,0%). Hasil penelitian bivariat menunjukkan hubungan usia (p = 0,009), Pendidikan (p= 0,015), pekerjaan (p = 0,007), paritas (p = 0,023), status anggota (p = 0,002), dan lama jadi anggota (p = 0,259) dengan tingkat kepuasan pasien BPJS yang mendapatkan pelayanan persalinan di Puskesmas Kecamatan Pulogadung Jakarta. Ada hubungan usia, Pendidikan, pekerjaan, paritas, status BPJS, dengan tingkat kepuasan pasien yang menerima layanan persalinan. Tidak ada hubungan lama jadi anggota dengan tingkat kepuasan pasien yang menerima layanan persalinan. Kata Kunci: Kepuasan Pasien, BPJS, Pelayanan Persalinan